STRATEGI KOMUNIKASI BMKG JUANDA DALAM PENGELOLAAN AKUN @infobmkgjuanda (Universitas Negeri Surabaya, 2023)
The weather has a significant influence on people's lives. This is the biggest reason information about the weather in an area is something that is needed by the community. But nowadays, people not only need information about the weather such as weather forecasts, but also education about the weather. The need for information about the weather does not stop at weather forecasts and education that explains events that have something to do with the weather alone, but the public also needs education about the weather that has the potential to trigger natural disasters. BMKG Juanda through his Instagram account, namely @infobmkgjuanda often uploads posts about education about weather. This study aims to understand how BMKG Juanda's communication strategy on his Instagram account. This research uses a case study method with data collection techniques, namely interviews, observations and documentation. The researchers findings were then analyzed using Phil Jones Communication Strategy Stage Theory. The result of this research is that in conducting education on his Instagram, BMKG Juanda carried out the stages of planning, implementing as well as follow-up and commitment.